Legislative Investigations into Propaganda Activities (1919–1941): The Tacit Collusion Between U.S. Politicians and the Press - Migliucci, Dario (Historia y Comunicación Social, 2021)
The present work analyzes the complex relationship that was established during the interwar period between the American press and the legislative committees which investigated the propaganda activities of subversive movements and large private corporations during those years. The investigation is the result of the examination of journalistic sources and documentary evidence recently collected from various US federal and state archives. The main hypothesis is that the struggle against propaganda by both the press and the legislative committees became a new form of manipulation of public opinion, enabling politicians and reporters to exploit people’s aversion to the new persuasion techniques in order to satisfy their own personal interests and ideological purposes.